Cell death and serum markers of collagen metabolism during cardiac remodeling in Cavia porcellus experimentally infected with Trypanosoma cruzi. - Yagahira E Castro-Sesquen; Robert H Gilman; Henry Paico; Verónica Yauri; Noelia Angulo; Fredy Ccopa; Caryn Bern (PLoS Neglected Tropical Diseases, 2013)
We studied cell death by apoptosis and necrosis in cardiac remodeling produced by Trypanosoma cruzi infection. In addition, we evaluated collagen I, III, IV (CI, CIII and CIV) deposition in cardiac tissue, and their relationship with serum levels of procollagen type I carboxy-terminal propeptide (PICP) and procollagen type III amino-terminal propeptide (PIIINP). Eight infected and two uninfected guinea pigs were necropsied at seven time points up to one year post-infection. Cell death by necrosis and apoptosis was determined by histopathological observation and terminal deoxynucleotidyl transferase dUTP nick end labeling, respectively. Deposition of cardiac collagen types was determined by immunohistochemistry and serum levels of PICP, PIIINP, and anti-T. cruzi IgG1 and IgG2 by ELISA. IgG2 (Th1 response) predominated throughout the course of infection; IgG1 (Th2 response) was detected during the chronic phase. Cardiac cell death by necrosis predominated over apoptosis during the acute phase; during the chronic phase, both apoptosis and necrosis were observed in cardiac cells. Apoptosis was also observed in lymphocytes, endothelial cells and epicardial adipose tissue, especially in the chronic phase. Cardiac levels of CI, CIII, CIV increased progressively, but the highest levels were seen in the chronic phase and were primarily due to increase in CIII and CIV. High serum levels of PICP and PIIINP were observed throughout the infection, and increased levels of both biomarkers were associated with cardiac fibrosis (p = 0.002 and p = 0.038, respectively). These results confirm the role of apoptosis in cell loss mainly during the chronic phase and the utility of PICP and PIIINP as biomarkers of fibrosis in cardiac remodeling during T. cruzi infection.